Stem Cells From the Apical Papilla (SCAP) as a Tool for Endogenous Tissue Regeneration - Nada, Ola A.; El Backly, Rania M. (Frontiers in Bioengineering and Biotechnology, 2018)
Stem cells extracted from developing tissues possibly exhibit not only unique but also superior traits against their developed counterparts. Indeed, stem cells from the apical papilla (SCAP); a unique group of dental stem cells related to developing roots have been shown to be a promising tool for regenerative endodontic procedures and regeneration in general. Studies have characterized the phenotypic traits as well as other regenerative potentials of these cells. Specific sub-populations have been highlighted as well as their neurogenic and angiogenic properties. Nevertheless, in light of the previously discussed features and potential applications of SCAP, there is still much to understand and a lot of information to unravel. The current review will discuss the role of specific markers for detection of different functional populations of SCAP; including CD146 and STRO-1, as well as their true multilineage differentiation potential. In particular, the role of the secretome in association with paracrine signaling in inflammatory microenvironments is also tackled. Additionally, the role of SCAP both in vitro and in vivo during regenerative approaches and in response to different growth factors and biologic scaffolds is highlighted. Finally, this review will shed light on current knowledge regarding the clinical translational potential of SCAP and elucidate possible areas for future research applications.